Portable immunosensor directly and rapidly detects Mycobacterium tuberculosis in sputum. Issue 4 (13th January 2022) - Ma, Jinbiao; Jiang, Guanyu; Ma, Qingqing; Du, Manman; Wang, Hao; Wu, Jianguo; Wang, Can; Xie, Xinwu; Li, Tie; Chen, Shixing; Zhang, Lixia; Wu, Min
Abstract : The immunosensor can complete the sputum detection directly within a few minutes, which greatly shortens the diagnosis time of TB. Abstract : Tuberculosis (TB) remains a public health problem that cannot be ignored. The portable and efficient detection of Mycobacterium tuberculosis (MTB) is important for the effective control of this disease. However, current detection techniques do not meet the requirements for MTB detection in the actual environment and often require cumbersome detection steps that are time consuming and inflexible. In this study, a portable immunosensor to detect MTB in sputum was prepared and then subjected to interface characterizations, such as scanning electron microscopy, hydrophilic angle test, and fluorescence characterization. The source and gate voltage of the device were optimized and tested using a non-contact photoresponse. The results showed that the sensitivity of the sensor to luminance increases with the decrease in source voltage. The gate voltage can substantially improve the response of the immunosensor to the normalized current of protein and amplify the signal at least 1.6 times. The optimal voltage detection conditions of source voltage (0.3 V) and gate voltage (0.1 V) were also determined. Several common proteins present in simulated saliva were used for anti-interference tests, and the sensor exhibited good specificity. Finally, the dilution gradient of an actual TB sputum sample was optimized. In the absence of preconditioning, a double-blind experiment was used to distinguish between the sputum from patients with TB and healthy individuals to shorten the TB detection time to a few minutes. Compared with the hospital's conventional detection method using cultures, the proposed method can complete the detection in a shorter time. This study provides a new strategy for the portable diagnosis of TB.